Pengaruh Earning Opacity, Kepemilikan Institusional, Intensitas Aset Tetap dan Inventory Intensity Terhadap Penghindaran Pajak - Karlin, Ani; Jelanti, Desi (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This study aims to determine and analyze the influence of earning opacity, institutional ownership, fixed asset intensity, and inventory intensity on tax avoidance. This type of research is a quantitative research, using secondary data that applies Microsoft Excel and E-Views 12. The population in this study is consumer cyclicals sector companies listed on the Indonesia Stock Exchange for the period 2018 to 2023. The data collection technique in this study is a purposive sampling technique with a total of 151 populations, so that the data samples obtained in this study are 15 samples. The results of the study show that earning opacity, institutional ownership, fixed asset intensity, and inventory intensity simultaneously affect tax avoidance. Then, the results of the study partially stated that earning opacity and fixed asset intensity had a negative influence on tax avoidance. Meanwhile, institutional ownership and inventory intensity have no effect on tax avoidance.